Plasticity in variation of xylem and phloem cell characteristics of Norway spruce under different local conditions - Gricar, Jozica; Prislan, Peter; De Luis, Martin; Gryc, Vladimir; Hacurova, Jana; Vavrčik, Hanuš; Čufar, Katarina (Frontiers in Plant Science, 2015)
There is limited information on intra-annual plasticity of secondary tissues of tree species growing under different environmental conditions. To increase the knowledge about the plasticity of secondary growth, which allows trees to adapt to speciﬁc local climatic regimes, we examined climate–radial growth relationships of Norway spruce (Picea abies (L.) H. Karst.) from three contrasting locations in the temperate climatic zone by analyzing tree-ring widths for the period 1932–2010, and cell characteristics in xylem and phloem increments formed in the years 2009–2011. Variation in the structure of xylem and phloem increments clearly shows that plasticity in seasonal dynamics of cambial cell production and cell differentiation exists on xylem and phloem sides. Anatomical characteristics of xylem and phloem cells are predominantly site-specific characteristics, because they varied among sites but were fairly uniform among years in trees from the same site. Xylem and phloem tissues formed in the first part of the growing season seemed to be more stable in structure, indicating their priority over latewood and late phloem for tree performance. Long-term climate and radial growth analyses revealed that growth was in general less dependent on precipitation than on temperature; however, growth sensitivity to local conditions differed among the sites. Only partial dependence of radial growth of spruce on climatic factors on the selected sites confirms its strategy to adapt the structure of wood and phloem increments to function optimally in local conditions.